Study of the Potential Value of Ilex affinis (Aquifoliaceae) as a Novel Source for the Food and Pharmaceutical Industries - Cogoi, Laura Carolina (2014)
Ilex paraguariensis St. Hilaire (Aquifoliaceae) is processed industrially to produce the commercial product “yerba mate” which is used as a tea-like beverage. It is one of the most commercialized plants of South America. It is exported to the US, Europe and Asia as vegetal drug or extracts used in complementary and alternative medicine and in formulations for functional foods due to its properties as a CNS stimulant, diuretic, weight reducing, antioxidant and antihypercholesterolemic, among others. Ilex affinis grows in the same habitat and is used as substitute or adulterant of I. paraguariensis. This species was never investigated before. The objective of this work was to assess the phytochemical composition and to determine the pharmacological activity, according with the major compounds present in it. The results showed small quantities of caffeine and theobromine, but a considerable amount of polyphenols, especially chlorogenic acid and isochlorogenic acid. I. affinis extracts presented scavenging activity on free radical DPPH in a concentration-dependent manner. Antiproliferative action on lymphoma cell line exerting both cytostatic and cytotoxic activities was also demonstrated.